2013
DOI: 10.1016/j.neuro.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic transcriptomic responses in the teleostean hypothalamus: A case study with the organochlorine pesticide dieldrin

Abstract: Organochlorine pesticides (OCPs) such as dieldrin are a persistent class of aquatic pollutants that cause adverse neurological and reproductive effects in vertebrates. In this study, female and male largemouth bass (Micropterus salmoides) (LMB) were exposed to 3 mg dieldrin/kg feed in a 2 month feeding exposure (August–October) to (1) determine if the hypothalamic transcript responses to dieldrin were conserved between the sexes; (2) characterize cell signaling cascades underlying dieldrin neurotoxicity; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Organochlorine pesticides are considered legacy pesticides, having been restricted or banned in use in the past three to four decades (e.g., methoxychlor, dieldrin); however there remain significant environmental exposure risks because OCPs are highly persistent in the environment and bioaccumulate in tissues (Gallagher et al, 2001; Martyniuk et al, 2013). One criterion to be considered for a chemical being classified as a direct-acting neuroendocrine disruptor is that the parent compound must cross the blood-brain barrier in order to exert central neuroendocrine effects.…”
Section: Legacy Pesticides As Neuroendocrine Disruptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organochlorine pesticides are considered legacy pesticides, having been restricted or banned in use in the past three to four decades (e.g., methoxychlor, dieldrin); however there remain significant environmental exposure risks because OCPs are highly persistent in the environment and bioaccumulate in tissues (Gallagher et al, 2001; Martyniuk et al, 2013). One criterion to be considered for a chemical being classified as a direct-acting neuroendocrine disruptor is that the parent compound must cross the blood-brain barrier in order to exert central neuroendocrine effects.…”
Section: Legacy Pesticides As Neuroendocrine Disruptorsmentioning
confidence: 99%
“…Male and female bass were fed 3 mg dieldrin/kg food over 2 months (Martyniuk et al, 2013). This concentration was selected to mirror environmental exposures that occur in contaminated sites, specifically the Superfund site of Lake Apopka in Central Florida.…”
Section: Legacy Pesticides As Neuroendocrine Disruptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…SNEA uses known relationships (i.e., based on expression, binding, and common pathways) between genes to build networks focused around gene hubs. This approach has been applied in biomarker discovery in mammals (Kotelnikova et al, 2012) and for gene and protein networks in teleost fishes (Martyniuk et al, 2012;Martyniuk et al, 2013a). Additional details can be found in the technical bulletin page 717 from Pathway Studios 7.0 as well as in Chishti et al (2013).…”
Section: Microarray and Bioinformaticsmentioning
confidence: 99%
“…Previous studies have shown that pollutants are capable of disrupting the neuroendocrine system of teleost fish, and many chemicals found in the environment can include neurotoxic mode of action (Martyniuk et al, 2013;Richter et al, 2014). These adverse responses in fish can include the modulation of the brain proteome.…”
Section: Introductionmentioning
confidence: 99%